(untitled) (Anclajes, 2024)
Psychology and cultural anthropology have dealt with shame. In the Western tradition, shame is usually analyzed in relation to sexuality, and homosexual variants were considered especially "shameful". It is only with the emergence of the Gay movement and Gay studies that a trend opposite to shame can be identified: pride in being gay. As a result, a lively debate about shame and pride is noted within gay communities, which is furthered by AIDS in the 1980s. A dichotomy between shame and pride then dominates the discourse, which is confirmed, for example, in the autobiographies of gay novelists who wrote before and after the turn of the millenium: in Juan Goytisolo and Luisgé Martín. While shame predominates in Goytisolo’s s texts, Luisgé Martín’s novels are not documents of pride, but his autobiography is, where a happily gay man speaks.